(untitled) (Journal of Computational Mathematics, 2019)
In this paper, we consider the scattering problem of time-harmonic electromagnetic waves from an infinite cylinder having an open arc Γ and a bounded domain D in R2 as cross section. We focus on the inverse scattering problem, that is, to reconstruct the shape of Γ and D from the far-field pattern by using the factorization method. Through establishing a mixed reciprocity relation, we prove that the scatters Γ and D can be uniquely determined by the far-field pattern. Furthermore, the mathematical basis is given to explain that the factorization method is feasible to our problem. At the end of this paper, we give some numerical examples to show the efficaciousness of the algorithms.